Dynamics of electrospinning of poly(caprolactone) via a multi‐nozzle spinneret connected to a twin screw extruder and properties of electrospun fibers. Issue 7 (30th November 2012) - Senturk‐Ozer, Semra; Ward, Daniel; Gevgilili, Halil; Kalyon, Dilhan M.
Abstract Conventional electrospinning is a simple process, suitable for the processing of solvated polymers at relatively low rates. It lacks the capabilities of conveying of solids, mixing of polymeric resins and devolatilization and has limited capabilities in melting and incorporation of fillers, including nanoparticles. The use of a twin screw extruder as the front end of the electrospinning process provides these capabilities but only becomes feasible at relatively high throughput rates. Such high rates of electrospinning can only be achieved by using multi‐nozzle spinnerets. However, the dynamics of electrospinning processes using multi‐nozzle spinnerets has not been well studied. Here a multi‐nozzle spinneret attached to a hybrid twin screw extrusion and electrospinning apparatus was employed for the characterization of the dynamics in terms of the electrospun mesh thickness distributions of poly(caprolactone), PCL, as a function of the principal parameters of the electrospinning process, i.e., applied voltage, distance of separation between the spinneret die, and the collector, i.e., a conductive mandrel, and its rotational speed. PCL fiber diameter and orientation distributions, as well as the thickness, crystallinity, and mechanical properties of the non‐woven meshes, were characterized to gain a basic understanding of how the electrospun mesh properties develop as a function of process parameters in the multi‐nozzle configuration. ENG. SCI., 2013. © 2012 Society of Plastics Engineers